2017
DOI: 10.21837/pmjournal.v15.i4.318
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Threats in the Preservation of the Traditional Malay Landscape

Abstract: The cultural landscape is regarded as being of the most complex designs which involves interactions between man, nature, cultural values and the associated built environment. Issues relating to the degradation of the cultural landscape are often caused by rapid urbanisation and industrialisation. The traditional Malay Landscape exists through harmoniously balanced interactions between man, nature and culture together with the traditional house, and contains unique and interesting features that have to be prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The cultural landscape is regarded as being of the most complex designs which involve interactions between man, nature, cultural values and the associated built environment (Harun et al, 2017). According to Sumardjo (2000), culture is a system of symbols which rely on the wearer, an organisation symptom (behavioural), objects (woodworking tools and production ideas (beliefs and knowledge) and sentiment (attitudes and values).…”
Section: Cultural Landscapementioning
confidence: 99%
“…The cultural landscape is regarded as being of the most complex designs which involve interactions between man, nature, cultural values and the associated built environment (Harun et al, 2017). According to Sumardjo (2000), culture is a system of symbols which rely on the wearer, an organisation symptom (behavioural), objects (woodworking tools and production ideas (beliefs and knowledge) and sentiment (attitudes and values).…”
Section: Cultural Landscapementioning
confidence: 99%
“…Some studies found that fragrant plants are mostly used and adopted in the traditional Malay landscape to portray Islamic concepts and elements (ibid). Moreover, Harun, Mohd Ariffin, & Abdullah (2017) found that diverse species of plants are related to everyday activities in a traditional Malay house. Whereby, Ramle, Shuaib, Abdullah, & Mat Rasat (2014) states that the type of plants growing in the Malay village has specific functions that are beneficial in the Malay daily of life such as fruit trees, herbs, or medicines.…”
Section: Significant Used Of Fragrant Plants In the Malay Way Of Lifementioning
confidence: 99%
“…On the other hand, archaeological research usually will only cost less than 5% of the total conservation cost of the building. Thus, it is misleading for many to consider archaeological research is expensive and hence to be omitted from conservation work (Caple, 2000;Harun, Ariffin, & Abdullah, 2017).…”
Section: Financial Implicationmentioning
confidence: 99%